Issues of Thin-Walled Sigma Beams Strengthened by CFRP Tape in the Context of Experimental and Numerical Studies - RZESZUT, Katarzyna; SZEWCZAK, Ilona; RÓŻYŁO, Patryk (Engineering Transactions, 2018)
In this paper, the results of laboratory tests and numerical analyses of thin-walled beams strengthened with carbon fiber reinforced polymer (CFRP) are presented. In particular, tensile tests of the steel and carbon fiber Sikar CarboDurr S tapes were conducted. Full scale laboratory tests included six sigma beams, each 140 mm high, 3 m long and with a wall thickness of 2.5 mm. The laboratory specimens were assumed as simply supported, single-span beams subjected to a uniformly distributed load. Four of the tested beams were reinforced with carbon fiber tapes, and the other two were not reinforced and were considered as reference beams. Numerical models of the considered beams were developed in the Abaqus program and subjected to validation and verification based on laboratory results. In the paper, special attention is paid to the evaluation of the possibility of increasing the critical load capacity while simultaneously limiting displacements of the beams by appropriate positioning of CFRP tape. The work completes with comparative analysis and conclusions.